Microfluidics-Based Single-Cell Research for Intercellular Interaction - Pang, Long; Ding, Jing; Liu, Xi-Xian; Kou, Zhixuan; Guo, Lulu; Xu, Xi; Fan, Shih-Kang (Frontiers in Cell and Developmental Biology, 2021)
Cell–cell communication is critical to numerous biology and medical studies, e.g., stem cell differentiation, immunotherapy and tissue engineering. Traditional methods employed for delving into cell-cell communication are limited by expensive equipment and sophisticated procedures. Microfluidics technique is considered as one of the powerful measures capable of precisely capturing and manipulating cells and achieving low reagent consumption and high throughput with decidedly integrated functional components. Over the past few years, microfluidics-based systems for cell–cell communication study at a single-cell level have become frequently adopted in biological and medical studies. This review covers microfluidics-based methods for cell–cell communication studies at a single-cell level. The challenges to be overcome in the future are highlighted.